NPL sebagai Pemoderasi Faktor-Faktor yang Mempengaruhi Audit Delay - Selvia Yunita; Indah Anisykurlillah (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2020)
This study aims to analyze the factors that influence audit delay in banking companies with the variables of management performance level, liquidity, complexity of company operations and reputation of audit firm with non-performing loans as moderating variables. The population in the study amounted to 43 banking companies listed on the Indonesia Stock Exchange for the period 2015-2019. Sampling was carried out by purposive sampling method which resulted in 28 samples during the 5 years of the study with a total of 140 units of analysis. The data analysis method uses moderation regression of absolute value difference. The results show that the level of management performance and KAP reputation have a negative effect on audit delay, while the liquidity and complexity of company operations have no effect on audit delay. Then non-performing loans are able to weaken the level of management performance, but are not able to weaken the liquidity and complexity of the company's operations due to audit delay. The conclusion in this study is that the higher the level of management performance, the shorter the audit delay, so the possibility of delay in audit reports is less likely